Pengaruh Pengungkapan Sustainability Information, Profitabilitas dan Capital Adequacy Ratio terhadap Nilai Perusahaan - Aulia Herani Safitri; Usep Syaipudin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
In 2022, Indonesia assumed leadership of the G20 Presidency. The subject "Recover Together, Recover Stronger" was selected, emphasizing the significance of coordinating economic and development policies. The primary concerns addressed included climate risk, the transition to a low-carbon economy, and sustainable financing. The Financial Services Authority (OJK) initiated the Indonesian Green Taxonomy as a framework for green economic activities and unveiled the Sustainable Finance Roadmap 2021–2025. This research investigates the impact of sustainability report disclosure, profitability, and the Capital Adequacy Ratio on the value of banking firms listed on the Indonesia Stock Exchange from 2019 to 2022. The study examines the influence of sustainability report disclosure, profitability, and Capital Adequacy Ratio on business value. The study employed a quantitative methodology and utilized secondary data from the annual report. The sample comprises 92 financial institutions, with the examined variables including the Sustainability Disclosure Reporting Index (SDRI), Return on Assets (ROA), Capital Adequacy Ratio (CAR), and price-to-book value (PBV) as an indicator of company value. Data were analyzed with SPSS 25. The findings indicate that sustainability report disclosure and ROA adversely impact business value, however CAR has a beneficial correlation with firm value. This study offers empirical data about the significance of sustainability reporting and financial performance in assessing business value within Indonesia's banking industry. This research highlights the significance of non-financial information in investment decisions and enhances the literature on sustainable finance and corporate governance.